Implementasi Sistem Monitoring Perangkat Rectifier dan AC Berbasis Jaringan VPN Menggunakan Mikrotik pada Ruang Server - Taufik Rahman; Muhammad Farid Anfasa Farid Anfasa (Fakultas Teknik Universitas Hamzanwadi, 2026)
Server rooms in the telecommunications sector require a reliable monitoring system to maintain service continuity, especially for supporting devices such as rectifiers and air conditioners (AC) which play an important role in power and temperature stability. A problem that often occurs is the limitation of monitoring that has not been integrated and cannot be accessed safely remotely, so it has the potential to cause delays in interference detection. This study aims to implement a monitoring system for rectifier devices and air conditioners based on the Virtual Private Network (VPN) network using MikroTik in the server room. The research methodology includes the stages of problem identification, literature study, system needs analysis, network topology design, VPN implementation and monitoring system, as well as testing and evaluating network performance. The VPN is configured on the MikroTik router to provide a secure communication path between the server room and the network administrator. The test was carried out by comparing the network conditions before and after implementation using connectivity parameters and monitoring access stability. The results of the study show that the proposed monitoring system is able to provide real-time monitoring of the condition of rectifiers and air conditioners with a better level of safety. MikroTik-based VPN implementations are proven to support stable and secure connectivity, thus speeding up the early detection process of interference and improving the operational reliability of server space. This system is expected to be a practical solution in managing server space infrastructure in telecommunication environments.